2018
DOI: 10.18203/2394-6040.ijcmph20185261
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance and its effect on academic performance among students of a medical college of Tripura

Abstract: Sleep deprivation is the condition of not having enough sleep; can be either chronic or acute. An average adult needs 7-9 hours of sleep each night, teenagers 9.5 hours and infants 16 hours per day. 3 College students are well known for keeping erratic sleep schedules. Sleep deprivation may have grave health consequences;ABSTRACT Background: Sleep deprivation may have grave health consequences; resulting in increasing disease morbidity and mortality. Sleep disturbance have also been affected academic performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
2
7
1
Order By: Relevance
“…The results for the sleep duration component revealed that the maximum (34.3%) participants were sleeping for 5-6 hours per night while 28% of participants were sleeping for less than 5 hours. Similarly, daily sleeping hours of 4-6 hours were reported by 69.38%[ 19 ] and 70.9%[ 20 ] participants in other studies. Also, 68.0% of the participants reported sleeping for 6-7 h per night in another study.…”
Section: Discussionsupporting
confidence: 58%
“…The results for the sleep duration component revealed that the maximum (34.3%) participants were sleeping for 5-6 hours per night while 28% of participants were sleeping for less than 5 hours. Similarly, daily sleeping hours of 4-6 hours were reported by 69.38%[ 19 ] and 70.9%[ 20 ] participants in other studies. Also, 68.0% of the participants reported sleeping for 6-7 h per night in another study.…”
Section: Discussionsupporting
confidence: 58%
“…Velten-Schurian et al [80] found that in children diagnosed with insomnia, those with more parent-reported nighttime awakenings tend to exhibit more daytime sleepiness. It has been previously reported that college students' daytime sleepiness is associated with GPA [40,84] and exam struggling [85]. The current study revealed that college students who have more difficulties staying awake throughout the day tended to get lower current and future GPAs, indicating the predictive power of daytime sleepiness in concurrent and future academic performance.…”
Section: Discussionsupporting
confidence: 50%
“…Study by Datta A et al revealed that students who got average mark in last semester exam were most affected with disturbed sleep (66.3%) followed by students who got good marks (53.5%) and poor marks (50%) which was statistically significant. [19] Lund HG et al reports that hyperarousal of autonomic nervous system and overactivation of hypothalamic-pituitary-adrenal axis can predispose; stressful events such as examinations and relationship problems can precipitate, and rumination and worry can perpetuate the sleep problems. [20] The present study, with 71 female and 67 male students revealed a significant association between gender and academic achievement, with the female students having better academic achievement, but no significant difference in level of sleep disturbance was found between female and male students.…”
Section: Discussionmentioning
confidence: 99%